STRATEGI PENINGKATAN PRODUKTIVITAS KERJA PETUGAS KARHUTLA RIAU BERBASIS BUDAYA K3 - Aziz Abdul; Iskandar “Is” (Eko dan Bisnis: Riau Economic and Business Review, 2026)
The Abstract : research was conducted by the Forestry Service, Forest and Land Fire Management Section of Riau Province, located on Jalan Sudirman, Pekanbaru, Riau. The purpose of this study was to examine the partial effect of occupational health on employee productivity, to determine the partial effect of occupational safety on employee productivity, and to determine the simultaneous effect of occupational health and safety on employee productivity. To achieve these objectives, the study used a sample of 42 people using a census method. The data analysis method used was multiple linear regression. Based on the test results for the occupational health variable, the calculated t-value was greater than the t-table (2.885 > 2.023). Thus, it can be concluded that the occupational health variable has a positive and significant effect on employee productivity. Based on the test results for the occupational safety variable, the calculated t-value was greater than the t-table (2.443 > 2.023). Therefore, it can be concluded that the occupational safety variable has a positive and significant effect on employee productivity. Based on the results of the hypothesis test, it was found that both occupational health and safety variables significantly influence employee productivity. The most dominant factor influencing employee productivity is occupational health. A recommendation is that the Forestry Service's Forest and Land Fire Management Section further improve the occupational health variable, as indicated by the percentage of 46.19% who stated they somewhat agreed. Therefore, it can be concluded that respondents/employees perceive that the occupational health program implemented by the service for employees is not being implemented effectively. If this continues, it will reduce employee productivity.   Keywords: Occupational Health, Occupational Safety, and Work Productivity